KARAKTERISTIK ALIRAN FLUIDA UNTUK PENGGUNAAN VORTEX GENERATOR DENGAN POSISI STRAIGHT PADA WING AIRFOIL NACA 0012 - Wawan Aries Widodo; Setyo Hariyadi; Bambang Junipitoyo; Gunawan Sakti; Supriadi Supriadi (Politeknik Penerbangan Surabaya, 2019)
Wings on an airplane have a very large effect on the formation of lift in all parts. From the wingtip area to the wingroot section, everything that happens between these parts will have an effect on the amount of lift produced. The use of vortex generators has a big influence with a small form of modification in the upper surface. The separation delay is an indication of the important things that are produced in its use. With this separation delay, the lift force will be greater and the drag force will be smaller. This is because the flow is better able to withstand friction and adverse pressure gradients. This study examines the flow across the NACA 0012 airfoil with the addition of a vortex generator. The vortex generator profile used is a flat plate vortex generator with a straight configuration and placed at x / c = 10% chord line direction from the leading edge. The variations used are the Reynolds (Re) number and the attack angle (Î±) on the airfoil. The freestream speed used is the speed of 12 m / s, and at the angle of attack (Î±) 0o, 3o, 6o, 9o, 12o, 15o, 17o, 19o, and 20o. The parameters evaluated included pressure coefficient (Cp), speed profile, lift coefficient, drag coefficient, and CL/CD ratio. The results of this study indicate that there was an increase in performance of the NACA 0012 airfoil with the addition of a vortex generator compared to without the use of a vortex generator. With the vortex generator more separation can be delayed. In this study also shows that the shape and arrangement of vortex generators play an important role in delaying separation.